2001
DOI: 10.1139/cjfas-58-3-506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ano×ia and sulfide on concentrations of total and methyl mercury in sediment and water in two Hg-polluted lakes

Abstract: Between May and December 1996, monthly samples of surface sediment (0-1 cm), settling matter, and water were taken at a shallow site and a deep site in each of two consecutive Hg-polluted riverine lakes. In the upper lake, the sediment was polluted also with cellulose fiber. Both hypolimnia turned anoxic, but sulfide was detected only in the upper lake. When sulfide appeared, hypolimnetic methyl mercury (MeHg) increased and reached 47 pM (9.4 ng·L -1 ), whereas MeHg in the sediment below decreased. The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…Factor 3 also groups a number of elements and compounds, such as Hg, methylmercury and sulphides, that are interrelated by natural processes occurring in reduced environments. Methylation of Hg is controlled by the activity of sulphate-reducing bacteria also producing sulphides, as already reported for different areas (Baeyens et al 1998;Regnell et al 2001). Besides the natural formation of sulphides in reducing environments, sulphide-bearing minerals from mining activities are also transported as suspended matter in the Tisza River (Osan et al 2002(Osan et al , 2007.…”
Section: Similar Behaving Metal Groups In Sediment Of Kiss Janosne Hosupporting
confidence: 53%
“…Factor 3 also groups a number of elements and compounds, such as Hg, methylmercury and sulphides, that are interrelated by natural processes occurring in reduced environments. Methylation of Hg is controlled by the activity of sulphate-reducing bacteria also producing sulphides, as already reported for different areas (Baeyens et al 1998;Regnell et al 2001). Besides the natural formation of sulphides in reducing environments, sulphide-bearing minerals from mining activities are also transported as suspended matter in the Tisza River (Osan et al 2002(Osan et al , 2007.…”
Section: Similar Behaving Metal Groups In Sediment Of Kiss Janosne Hosupporting
confidence: 53%
“…The extracellular speciation of heavy metals has been demonstrated to be an important determinant of its biological uptake (). So far it has been shown that passive diffusion is a key mechanism for Hg uptake by Hg methylating bacteria in both lab culture work ( 15−17 , 23 ) and fieldwork ( ) because of the stronger bioavailability of small-size neutral-charged Hg complexes. Comparisons of diffusion rates through the aqueous unstirred layer and through the cell membrane show a difference of several orders of magnitude, indicating that the latter is the limiting step of Hg transport to cells ( , ).…”
Section: Resultsmentioning
confidence: 99%